2022
DOI: 10.1002/cctc.202200266
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Silica‐Alumina as Suitable Catalyst for the Diels‐Alder Cycloaddition of 2,5‐Dimethylfuran and Ethylene to Biobased p‐Xylene

Abstract: The potential of amorphous silica-alumina (ASA) to substitute zeolites (HBeta-25) for the synthesis of p-xylene via Diels-Alder cycloaddition (DAC) of ethylene to 2,5-dimethylfuran (2,5-DMF) is investigated. ASA were prepared via homogeneous deposition-precipitation of Al on SiO 2 . ASA shows good yields of pxylene (20-25 % after 18 hours) compared to bare silica and γalumina. Brønsted acid sites (BAS) were identified as the active sites for the DAC reaction. The catalytic performance correlated strongly with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…aConcentration of the total Brønsted (1545 cm −1 ) and Lewis (1455 cm −1 ) was obtained after evacuation of pyridine at 150 °C, while the concentration of strong Brønsted was determined after evacuation at 400 °C.bAmount of Brønsted acid sites obtained after peak fitting of the CO saturated sample.cIR band position of the CO–OH complex.dData were taken from ref. 24.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…aConcentration of the total Brønsted (1545 cm −1 ) and Lewis (1455 cm −1 ) was obtained after evacuation of pyridine at 150 °C, while the concentration of strong Brønsted was determined after evacuation at 400 °C.bAmount of Brønsted acid sites obtained after peak fitting of the CO saturated sample.cIR band position of the CO–OH complex.dData were taken from ref. 24.…”
Section: Resultsmentioning
confidence: 99%
“…Although not investigated in this work, previous studies have shown that ASA prepared by the grafting of Al shows higher stability in the DAC reaction compared to the zeolite benchmark. 24 This has been linked to the absence of Al leaching from the ASA surface and the poor structural integrity of the HBeta crystal upon consecutive reuse. 24,33…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations